The Effect Of Use Audio Visual Media On Passing Ability In Futsal - Agus Nugraha; Ribut Wahidi (Journal of Physical Education and Sport Science, 2019)
The purpose of this study was to determine the different effects of using audio-visual media on the passing ability of futsal sports, to find out how much influence the use of audio-visual media has on the passing ability of futsal sports. This research method is an experimental method with the research design of One-Group Pretest-Postest Design. The sample used was 25 grade VII students at MTs Darussalam Japara. The research results obtained by researchers from the results of the calculation of the T test paired sample test explained that there is an effect of the use of audio visual media on the ability to pass in futsal sports.